2017
DOI: 10.9734/ajaees/2017/33636
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Adoption of Drip Irrigation System by the Farmers in Bikaner District of Rajasthan

Abstract: Water is a most precious natural resource and vitally important for agricultural development and day-today living. In order to use such a precious natural resource economically, drip irrigation would be a possible solution which minimizes the losses of water and fertilizer as well as increase the yield of crops. The present study was conducted in four panchayat samities (out of six) in Bikaner district of Rajasthan on the basis of highest area and large number of beneficiary farmers under drip irrigation syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Jumanne (2016) put forth that the farmers' age, education levels and other economic factors have influenced technology adoption. Similar results reported by Verma & Sharma (2017) in Rajasthan where it was reported that varied variables such as education levels, annual income, mass media exposure etc. had a positive and significant relationship with drip irrigation adoption.…”
Section: Association Of Socio-economic Factors With the Knowledge And...supporting
confidence: 87%
“…Jumanne (2016) put forth that the farmers' age, education levels and other economic factors have influenced technology adoption. Similar results reported by Verma & Sharma (2017) in Rajasthan where it was reported that varied variables such as education levels, annual income, mass media exposure etc. had a positive and significant relationship with drip irrigation adoption.…”
Section: Association Of Socio-economic Factors With the Knowledge And...supporting
confidence: 87%
“…It is recommended that policy makers and private sector should consider socio-economic factors when mainstreaming small holding farmers in horticulture industry production and productivity. Verma & Sharma (2017) also reported that variables like knowledge, education, social participation, annual income, economic motivation and mass media exposure were found positively and significantly associated with the adoption of drip irrigation by the farmers. While, size of land holding, experience in farming and irrigation potentiality were found non-significantly associated with the adoption of drip irrigation by the farmers.…”
Section: Adoption Level Of Drip Irrigation and Socio-economic Factorsmentioning
confidence: 89%
“…The drip irrigation technology is particularly well suited to saline and alkaline soils, with a water consumption efficiency of 80 to 90 per cent. (Verma & Sharma, 2017). In India, the area under drip irrigation has increased dramatically during the previous 15 years.…”
Section: Introductionmentioning
confidence: 99%
“…Thakur and Sharma [8] in their study found that the most of respondents had a metric level of education (50%), followed by a bachelor's degree (25%), higher secondary education (22.5%), and graduate research (2.50%). Verma et al [14] in their study, factors Associated with Adoption of Drip Irrigation System by the Farmers in Bikaner District of Rajasthan found that 14.53 per cent of the people asked were illiterate and 32.48 per cent were literate up to elementary school. Similarly, 23.51, 15.81, and 8.97 per cent of respondents belonged to the categories of secondary, secondary, and higher secondary education, respectively.…”
Section: Deshmukh Et Almentioning
confidence: 99%